Land Cover of Mangrove Ecosystem in Marine Tourism Integrated Mandeh Sub-District Koto XI Tarusan, Pesisir Selatan Regency - Agustian, CH.; Kamal, Eni; Mustapha, Muzzneena Ahmad; Putra, Aprizon (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
Mangrove is a plant that can live in tidal areas and form a community of independent vegetation, ranges to various disorders, especially marine resource management that is not environmentally friendly causing damage to the Mangrove forest. Thus researched to know the condition, the rate of change in land area and public response to the mangrove ecosystem implemented in August 2019 using Phantom 4 Drone data and a descriptive method Quantitative. The results were adopted, namely, the condition of the mangrove ecosystem was declared normal (0.22) in the year 2009 using NDVI value classification, as well as the year 2019 NDVI value of 1 in the condition is very good. The area on land cover amounted to 406.61 ha in 2019, while the year 2009 amounted to 406.69 ha with a change of-0.08 ha. Mangrove conditions with an area of 79.13 ha in 2009, a decline in 2019 of 60.01 ha, a change of-19.12 ha (-24.16%). The mangrove ecosystem is getting worse because of the road construction that causes some material to fall into the mangrove area that makes the sedimentation wider, as occurs in the segment 3 The change of mangrove overflow from the year 2009 (21.60 ha) 19.83 ha in the year 2019. People are still promoting the economy compared to the survival of mangroves because the existence of mangroves is considered economically beneficial for them.